The effect of polycaprolactone/graphene oxide electrospun scaffolds on the neurogenic behavior of adipose stem cells - PINAR, ERTUĞRUL; ÜNAL YILDIRIM, SEMRA; GÜNDÜZ, OĞUZHAN; HARMAN, FERHAT (My University, 2022)
Stem cell destiny can be controlled with scaffold biomaterials in tissue engineering and regenerative medicine. This study aimed to investigate the neuronal differentiation potential of human adipose tissue-derived mesen- chymal stem cells in graphene nanofiber matrix in vitro. Stem cell isolation was performed from adipose tissue taken from human by mechanical and enzymatic methods. The differentiation potential was examined after incubation of adipose stem cells in normal medium and neural differentiation medium, on graphene oxide (GO) and polycaprolactone (PCL) composite scaffolds produced by electrospinning technique. In vitro studies indi- cated that the presence of GO in PCL scaffold increases an effect on cell attachment, proliferation, infiltration into the scaffold, and neuronal differentiation. Also, unlike subcutaneous tissue, it has been shown immunohis- tochemically that mesenchymal stem cells derived from epidural adipose tissue tend to differentiate into oligodendrocytes.
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED)